Effect of Acute Physical Exercise with Moderate Intensities on FGF23 Gene Expression in Wistar Rat Heart - Vita Murniati Tarawan; Julia Windi Gunadi; Tiodora Arimenda Br. Subekti; Wahyu Widowati; Hanna Goenawan (Majalah Kedokteran Bandung, 2019)
A myokine is one of the proteins that are produced and released by myocytes in response to muscular contractions when doing physical exercise. One protein that is thought to function as myokine is FGF23.The purpose of this study was to determine the effect of acute physical exercise with moderate intensity on the expression of FGF23 gene in Wistar rat heart. This was an animal experimental study using 24 male Wistar rats that were divided into 4 groups:treatment groups that performed 30 minute acutephysical exercise with moderate intensity (20 m/min) for 3 days, 6 days, and 15 days and a control group without physical exercise. The study was conducted in the Animal Laboratory and Central Laboratory of Universitas Padjadjaran during the period of February to July 2019. Data observed were the FGF23 gene expressions in Wistar rats heart. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. The results from the Kruskal-Wallis test showed that acute physical exercise with moderate intensity did not increase the FGF23 gene expression in Wistar rat heart (p>0.05), and the average of relative ratios of FGF23/GAPDH gene expression were as follows: control (0.970±0,03), 3 days (0.992±0.03), 6 days (1.014±0.05), and 15 days (1.056±0.02). GAPDH was used in this study as a housekeeping gene since its expression is very constant. This study proves that FGF23 is more likely to take a role in the cardiac remodeling process, especially those associated with cardiac hypertrophy after chronic exercise with no effect observed after acute physical exercise with moderate intensity in Wistar rat heart. Pengaruh Latihan Fisik Akut Intensitas Sedang terhadap Ekspresi Gen FGF23 pada Jantung Tikus Galur WistarMiokin diproduksi dan dilepaskan oleh miosit sebagai respons terhadap latihan fisik. Salah satu protein yang diduga berfungsi sebagai miokin adalah FGF23. Penelitian ini bertujuan mengetahui pengaruh latihan fisik akut intensitas sedang terhadap ekspresi gen FGF23 pada jantung tikus galur Wistar. Penelitian ini menggunakan desain eksperimental dengan tikus galur Wistar jantan yang berjumlah 24 tikus. Tikus dibagi menjadi 4 kelompok untuk diberi perlakuan latihan fisik intensitas sedang (20 meter/menit) dengan durasi 30 menit, selama 3 hari, 6 hari, dan 15 hari serta kelompok tanpa latihan fisik. Penelitian ini dilakukan di Lab Hewan dan Lab Sentral Universitas Padjadjaran pada bulan Februari hingga Juli 2019. Ekspresi gen FGF23 pada jantung tikus galur Wistar dilihat dengan PCR. Analisis data menggunakan uji Kruskal-Wallis dan Mann-Whitney. Uji statistik tidak mendapatkan peningkatan ekspresi gen FGF23 setelah dilakukan latihan fisik akut intensitas sedang selama 3 hari, 6 hari dan 15 hari (p>0,05) dan didapatkan rasio relatif ekspresi gen FGF23/GAPDH otot jantung pada : kontrol (0,970±0,03), hari 3 (0,992±0,03), hari 6 (1,014±0,05), hari 15 (1,056±0,02). GAPDH digunakan dalam studi ini sebagai gen ‘housekeping’ karena ekspresinya yang sangat konstan. Studi ini membuktikan bahwa FGF23 mungkin lebih berperan dalam proses remodeling jantung, terutama yang berhubungan dengan hipertrofi jantung setelah latihan fisik kronik. Simpulan, tidak terdapat pengaruh latihan fisik akut intensitas sedang terhadap ekspresi gen FGF23 pada jantung tikus galur Wistar.